Keberkesanan Organisasi dalam Penyampaian Perkhidmatan: Penilaian Berdasarkan Paradigma Servqual dan Model Kano (Journal of Business Management and Accounting, 2015)
Departments under the government sector needs to offer the best quality service to meet the needs and requirements of customers. At the same time, the departments should ensure that service delivery to the customer is always relevant from time to time in line with Malaysia government policies, changes in technology, economic development and the dynamics of consumer preferences. The main objective of this study are to measure the quality of service delivery by Department MG using paradigma SERVQUAL and to measure customer satisfaction against the services offered using the Kano Model. Based on paradigma of SREVQUAL, the findings show 20 items out of 21 items that are measured situated in very strong position. Based on Kano model, the findings also shows the level of customer satisfaction are at 79-75% per cent. This indicates MG Department has successfully met the needs and requirements of its customers. But to remain competitive in the services market, MG Department needs to improve the items that are rated below 75%. The results obtained will help improve the performance of the Department MG in offering services to its customers. It is in line with government policy, namely people first, performance now. In fact, the results can be used as a guide in the development of policy and strategy of departments under government sector.